Islam Nusantara and Local Traditions: Role and Challenges in Indonesia’s Cultural Diplomacy and International Relations - Damayanti, Rizki (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This paper explores Islam Nusantara, an Indonesian expression of Islam that blends local culture with Islamic teachings, and its role in cultural diplomacy. Using qualitative methods and literature review, the study traces its historical development and core values such as moderation (wasatiyyah), tolerance, and peaceful coexistence. The result shows that these values allow Indonesia to employ Islam Nusantara as a soft power tool to promote religious tolerance, dialogue, and peaceful engagement, particularly in Muslim-majority and multicultural societies. However, challenges persist, including debates on its authenticity and tensions between local practices and global Islamic discourses. The paper concludes that the dynamic interaction between local Islamic traditions and international diplomatic strategies strengthens Indonesia’s soft power and role in global intercultural cooperation. Islam Nusantara offers a compelling model for how indigenous Islamic practices can support peacebuilding and enhance international relations.